PENGARUH PENGGUNAAN FACEBOOK TERHADAP PARTISIPASI MASYARAKAT DALAM MENJAGA KEAMANAN DAN KETERTIBAN KOTA MANADO - Whitney Kenny Rey Pangkey; Rully Viersa Budiman; Sekar Puspita Dewi (Jurnal Pustaka Komunikasi, 2022)
Facebook is one of internet-based social interaction platform for the community to participate in various agendas. In Manado, people use Facebook as communication media to participate in maintaining security and order around them. This study focuses on phenomena that occur in society that involve the influence of social media, especially Facebook on public participation in maintaining community security and order of Manado. This study uses the ‘uses and gratifications theory’ as the main theory, where the research method used in this study is a quantitative research method using a questionnaire resulting in a strong relationship between the use of Facebook and public participation in maintaining public security and order in Manado City. This research can be used as basic information for Manado residents to be more aware of circulating criminal issues.